Validation of a chloroquine-induced cell death mechanism for clinical use against malaria - Ch'ng, J.; Lee, Y.; Gun, S.; Chia, W.; Chang, Z.; Wong, L.; Batty, Kevin; Russell, B.; Nosten, F.; Renia, L.; Tan, K. (Nature Publishing Group, 2014)
An alternative antimalarial pathway of an ‘outdated’ drug, chloroquine (CQ), may facilitate its return to the shrinking list of effective antimalarials. Conventionally, CQ is believed to interfere with hemozoin formation at nanomolar concentrations, but resistant parasites are able to efflux this drug from the digestive vacuole (DV). However, we show that the DV membrane of both resistant and sensitive laboratory and field parasites is compromised after exposure to micromolar concentrations of CQ, leading to an extrusion of DV proteases. Furthermore, only a short period of exposure is required to compromise the viability of late-stage parasites. To study the feasibility of this strategy, mice malaria models were used to demonstrate that high doses of CQ also triggered DV permeabilization in vivo and reduced reinvasion efficiency. We suggest that a time-release oral formulation of CQ may sustain elevated blood CQ levels sufficiently to clear even CQ-resistant parasites.